OPTIMALIZATION OF MICROSTRIP SLOT ARRAY ANTENNAS FOR MULTI-WIDEBAND - Fitri, Iskandar (Indonesian Journal of Aerospace, 2007)
Microstrip slot antenna fed by matching network of microstrip line to increase very wide-bandwidth and multiband is proposed. The microstrip line composed of multi tuning stubs is used to control slots antenna real impedance to match with impwdance cahracteristic of feeding line so that it could increase the bandwidth. The design are achieves good input impedance in the ranges frequency of 1.3 - 5.1 GHz for single slot and 1.1 - 6.4 GHz for two slots. The bandwidths of antennas become very wide if the slots made in array configuration. The measured return loss S11 agrees well with the simulation results for single slot as axample. Keywords: microstrip slot antenna, array configuration, network impedance, multi tuning stub.